Acidente com material biológico: risco, perfil e preparo do acadêmico de enfermagem - Cardoso, Najara Queiroz (2015)
For nursing staff the biohazard is a major concern with physical and emotional impact on the health of these workers, with the graduates of this area under the same risk. The objectives of this study were to analyze the epidemiology of accidents with biological material involving nursing students in the scientific literature; describe the frequency and profile of accidents with biological material among nursing students of a higher education institution; identify activities of academic practice considered risk for accidents with biological material in the view of nursing graduates; characterize the preparation of the nursing academic front of an accident with biological material. This study results were presented in the form of two articles, the first being an integrative review of the literature on accidents involving biological material among nursing students, the descriptor available in the Descriptors in Health Sciences of the Virtual Health Library and the Medical Subject Headings in the PUBMED electronic databases Literature Analysis and Retrieval System Online (MEDLINE), Latin American and Caribbean Health Sciences (LILACS), Cumulative Index to Nursing and Allied Health Literature (CINAHL), no time frame. They found 1849 articles, these 37 met the inclusion criteria. The investigated items showed that the profile of accidents with biological material among undergraduate students follow the same profile of affected by nursing professionals and are associated with the lack of biosecurity measures, post-exposure recommendations and other factors intrinsic to the vocational training process . The second article was a cross-sectional descriptive study by means of an electronic questionnaire with the third nursing students the tenth periods of a public institution of higher education in the state of Goiás. The study was approved under protocol nº414258. The study included 126 undergraduate students with a mean age of 21.6 years. Among the activities of nursing practice the sharps handling was the most cited (64.4%) and 98.4% of the students said to have received prior guidance on the possibility of contact with body fluids during the course of practical activities. However, most did not know how to describe the post-exposure measures. There were four accidents (3.2%), more frequent exposure of the ocular mucosa (75.0%) with the blood longer present as biological material. Two students reported accidents to teachers who have followed all recommended behaviors. It was found that the communication of the accident to the teacher resulted in adherence to recommended post-exposure measures.